2021
DOI: 10.3389/fsurg.2021.668928
|View full text |Cite
|
Sign up to set email alerts
|

Tips and Tricks to Improve Ergonomics, Efficacy, Versatility, and Overcome Limitations of Micro Percutaneous Nephrolithotomy

Abstract: Percutaneous Nephrolithotomy (PCNL) has evolved over the decades from Standard to Mini to Ultramini PCNL to Micro-perc, with miniaturisation being the dominant theme and supine approach gaining momentum world over.Aim: In literature, miniaturised PCNL with microperc needle access system has raised concerns of intrarenal pressure and has some limitations with its success for larger stones. Our tips and tricks explain how to overcome these pitfalls by utilising the full construct of the needle system to its maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…Tiny fragments can be flushed through the PCNL sheath or ureteral access sheath (UAS). 55 Based on the findings of this review, there are advantages of ECIRS over PCNL. Apart from the outcomes analyzed in this review, several studies suggest the ease of performing the procedure, including the avoidance of the need for multiple tracts and the improvement of helping decide the need for a ureteral stent or a second-stage procedure.…”
Section: Discussionmentioning
confidence: 94%
“…Tiny fragments can be flushed through the PCNL sheath or ureteral access sheath (UAS). 55 Based on the findings of this review, there are advantages of ECIRS over PCNL. Apart from the outcomes analyzed in this review, several studies suggest the ease of performing the procedure, including the avoidance of the need for multiple tracts and the improvement of helping decide the need for a ureteral stent or a second-stage procedure.…”
Section: Discussionmentioning
confidence: 94%
“…From their side, S. Biligere et al reported the successful experience of a combination of micro-PNL (nephroscope tube size 7-11 Fr) and RIRS. In this combination, percutaneous and retrograde endoscopic accesses to the renal collecting system were also performed, but the evacuation of calculus fragments, in contrast to the mini-PNL, was performed through a retrograde ureteral introducer [49].…”
Section: Resultsmentioning
confidence: 99%